II International Academic Forum “Actual Problems of Study and Preservation of Historical and Cultural Legacy of the Crimea” Dedicated to the Memory of Mengli Giray » - E.E. Abibullaeva (Золотоордынское обозрение)
From 30 October to 1 November 2015, the Crimean Research Centre of Sh.Marjani Institute of History of Tatarstan Academy of Sciences successfully held in the city of Bakhchisaray the II International Academic Forum “Actual Problems of Study and Preservation of Historical and Cultural Legacy of the Crimea” Dedicated to the Memory of Mengli Giray. 60 participants from different regions of Russia, Ukraine, Belarus, Azerbaijan took part in the Forum. Speakers highlighted the most urgent issues and proposed solutions and implementation of the study and preservation of historical and cultural heritage of the Crimea. During the forum, four round tables were held to the following issues: “The Role of Preservation of Historical and Cultural Heritage and Development of the Tourist Potential of the Republic of Crimea”, “Problems of Preservation and Study of the Historical Heritage of the Crimea”, “Philology, Ethnography, Art and Culture of the Crimean Ethnic Groups: Traditions and Contemporaneity”, “Women’s Diplomacy Day” dedicated to the memory of Nur Sultan. The Forum was concluded with a visit to the exhibition in Zyndzhyrly madrassas (historical and architectural monument of the 16th century, Crimean Republican Institution “Bakhchisaray Historical, Cultural and Archaeological Museum-Reserve”) “Tugra and the Universe” (by I.Sheikh-Zade), in which the material from the eponymous work by Mirkasym Usmanov was used.